Gastrointestinal Tract Symptomatology in Adults with Pica and Autism - D.D. Alexander; S.E. Lunde; D.E. Berger (Moscow State University of Psychology and Education, 2020)
This study investigated pica behavior in those with and without autism in relation to gastrointestinal (GI) tract symptomatology and disease. A chart review of 64 residential adults with developmental disabilities indicated that individuals with pica had more GI tract diseases, and those with autism and pica had a higher rate of GI diseases compared to those with autism and no pica behavior. These data suggest that individuals with both autism and pica disorders may be a phenotypic subgroup in the autistic spectrum characterized by GI symptomatology, requiring a clinical algorithm for categorization and effective treatment. A behavior-analytic model is presented that conceptualizes pica as part of a chain of events that begins with exploratory behavior and culminates in GI symptomatology and disease. Issues of sensory processing are addressed within this model. Individuals exhibiting pica may benefit from gastrointestinal evaluation, including assessment of the microbiome, and, if indicated, microbiota transfer therapy to